2016
DOI: 10.1186/s13063-016-1317-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of pharmaceutical care for drug treatment adherence in patients with systemic lupus erythematosus in Rio de Janeiro, Brazil: study protocol for a randomized controlled trial

Abstract: BackgroundTreatment adherence is a primary determinant of the success and effectiveness of healthcare. Lack of adherence can lead to treatment failure and death. Although studies have shown that pharmaceutical intervention can improve drug treatment for patients with chronic diseases, studies on pharmaceutical care are not only inconsistent, they are scarce and limited to developed countries, include few patients, and are not studied in randomized clinical trials. Systemic lupus erythematosus is an autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Drug withdrawal trials57 or trials that use flare for inclusion or outcome could also be considered as they allow the participation of patients with more severe disease. Novel designs might focus on reducing the impact of placebo response, including placebo response related to pretrial non-compliance 58 59. In considering targets of treatment, it is tempting to focus on autoimmune inflammatory manifestations where exciting new discoveries provide novel targets 60.…”
Section: Resultsmentioning
confidence: 99%
“…Drug withdrawal trials57 or trials that use flare for inclusion or outcome could also be considered as they allow the participation of patients with more severe disease. Novel designs might focus on reducing the impact of placebo response, including placebo response related to pretrial non-compliance 58 59. In considering targets of treatment, it is tempting to focus on autoimmune inflammatory manifestations where exciting new discoveries provide novel targets 60.…”
Section: Resultsmentioning
confidence: 99%
“…Durcan et al, in 2015, reported that the blood level of the prescribed medication may not correspond to the quantity administered to the patient because of non-adherence to treatment. Adherence to treatment in LE and RA ranges from 31.7% to 45.9% (6,21,(22)(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…31 In this study, patients were considered adherent when they answered negatively to all points of the MTA questionnaire, and adherence was considered a dichotomous variable. 32…”
Section: Methodsmentioning
confidence: 99%